KUR'AN IŞIGINDA DÜŞÜNCE, iNANÇ VE iFADE HÜRRiYETi - Güneş, Abdulbaki (Fırat University, 2005)
According to the Qur'an no one has the right to oppress or interfere wıtlı anya ne 's fa ith or beliejs. Human beings are completely free to believe or not to believe anything they choose wlıetlıer they practice or not wlıat they believe in. In Islam ılıere is no place for oppression or suppression of any kind whatever the conditions. Freedam is of vi ta! importance in Islam; without it ne it her a lıealtlıy development of one 's abilities is passibi e nar can one be he/d responsibi e for lıisl/ıer actions. lt plays a key role in every aspect of the islami c way of life. Belief and fa ith in islam are not just a passive submission but a process of searching and inquiring. islam invites all adherents and non-Muslims to think and reason on even basic principles of the religion. Islam has banned all sorts of belittling. No one .:an be b/amed or mocked because of his/her beliejs, ıvay of life or worldview. No one is entitled to force sameone to change Jıislher li kes or dislikes. The Qur 'an advises all Muslims i ncluding non-Muslinıs to respect each other, to act honestly. to treat people equally and create a peacefiıl environment. No Muslim is allawed to do any injustice to anyone be it a believer or inat. A Muslim has the riglıt of defending his faith and beliejs ıvlıile respecting otlıer's freedam of doing the same thing. In that respect ılıere is no discrimination between a Muslim and non-A1uslim. According to islam the riglıt of believing is basically a human riglıt; one can reveal, without any restraint, lıis/lıer belief Freedam in islam is alması unrestricted as long as the right and freedam of other individuals is not vıolated. And this places Islam in a ımique pasifian among other religions.
Keywords: Religious Studies; Din Araştırmaları